Creating Pop-up books : a strategy focused on English process writing skills of sixth graders. (2021)
This research explores the development of writing skills in English as a foreign language of sixth graders through three-dimensional paper mechanisms in the creation of a pop-up book. Crafting and source culture will be developed while students learn a foreign language. The research is meant to improve writing skills of young learners using three stages of writing (Pre-writing, Writing, and Re-writing). Thus, the use of Process Writing Approach is necessary to have a whole knowledge development. Through process writing, source culture awareness, and crafting abilities, students will create a pop-up book about one complete and simple Colombian indigenous legend. Therefore, young learners are supposed to write in different stages to acquire English language writing skills while creating their pop-up book.